The development and establishment of the 1st WHO BKV International Standard for nucleic acid based techniques. (July 2019) - Govind, Sheila; Hockley, Jason; Morris, Clare; Almond, Neil; ,
Abstract: Immunocompromised patients are at significant risk from BKV reactivation, causing allograft dysfunction or loss. Patient management relies on viral DNA monitoring, using a viral load cut-off to reduce immunosuppression. However, consistency between viral load detection assays cannot be achieved without an effective means of standardisation. We have worked with the WHO's Expert Committee on Biological Standardisation to develop suitable reference materials and undertake an international collaborative study to establish the 1st WHO International Standard for BKV detection assays. We report on the evaluation of two lyophilised candidate cell culture derived, whole virus preparations, undertaken by 33 expert laboratories. By employing the principles of biological standardisation, we show improved agreement across laboratories, demonstrating the suitability of either candidate for use as a primary order calibrant. Candidate 14/212 was established by the WHO ECBS with an assigned potency of 7.2 log10 International Units/mL intended for the calibration of BKV secondary reference materials.